2007
DOI: 10.1186/1742-4690-4-62
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus type 1 specific cytotoxic T lymphocyte responses in Chinese infected with HIV-1 B'/C Recombinant (CRF07_BC)

Abstract: Background: The characterization of HIV-1-specific T cell responses in people infected with locally circulating HIV-1 strain will facilitate the development of HIV-1 vaccine. Sixty intravenous drug users infected with HIV-1 circulating recombinant form 07_BC (CRF07_BC), which has been spreading rapidly in western China from north to south, were recruited from Xinjiang, China to assess the HIV-1-specific T cell responses at single peptide level with overlapping peptides (OLP) covering the whole concensus clades… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
(82 reference statements)
2
4
0
Order By: Relevance
“…Additionally, in these studies (18,22,28) and our study, concordant and discordant responses are found. This phenomenon can be explained by (i) amino acid substitutions within the optimal epitope, (ii) substitutions in close proximity to the optimal epitope, and (iii) the relative position of the optimal epitope within a given peptide (peptide offsetting).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Additionally, in these studies (18,22,28) and our study, concordant and discordant responses are found. This phenomenon can be explained by (i) amino acid substitutions within the optimal epitope, (ii) substitutions in close proximity to the optimal epitope, and (iii) the relative position of the optimal epitope within a given peptide (peptide offsetting).…”
Section: Discussionsupporting
confidence: 74%
“…Initial reports included only subtype B-or C-infected patients (1,(47)(48)(49), but more recently other subtypes and CRF recombinant forms are being studied (18,22,27,28,35). On the other hand, the immunoprotective role of HIV-specific vaccine-induced T cells may be limited by the large genetic distance between viral strains circulating in different locations and the vaccine strain.…”
Section: Discussionmentioning
confidence: 99%
“…CTLs recognize fragments of viral proteins (CD8 epitopes) that are presented by HLA on the infected cell surface and subsequently kill the infected cell. Numerous studies have observed that CTLs frequently target CD8 epitopes in Vif (92)(93)(94)(95)(96)(97)(98). The pleiotropic effects of CTL-induced escape mutations that prevent viral recognition and the killing of infected cells depend on the affected Vif region and may destabilize the interactions between Vif and APOBEC3F, APOBEC3G, and/or other deaminases or the interactions between Vif and Elongin C. The importance of the specific Vif sequence in determining the biological outcome of the interaction between Vif and a range of APOBEC3 proteins is emphasized by reports demonstrating that, e.g., APOBEC3C and APOBEC3B are neutralized by some Vif variants but not others (40) and that Vif subtype variability affects the efficiency of the interaction with APOBEC3G (99).…”
Section: Figmentioning
confidence: 99%
“…Median CD4 counts and plasma viral loads at the time of sampling were 378 cells/mm 3 (full range: 50–940 cells/mm 3 ) and 20,700 copies/ml (full range: <50–714,000 copies/ml), respectively (Table S1). Subjects became infected through sharing contaminated needles during drug use, and subjects were confirmed to be infected with CRF07_BC strain162526 (Table S1). The historical neutralization data of 103 subjects from the FPD cohort15 with over ten years’ infection time were used to compare with those generated in the IDU cohort.…”
Section: Methodsmentioning
confidence: 99%
“…Our laboratory previously studied the biological and virological characteristics25 and cytotoxic T lymphocyte (CTL) response pattern26 of CRF07_BC infection. However, the humoral response pattern during infection caused by this unique recombinant subtype has not yet been adequately investigated.…”
mentioning
confidence: 99%